Analysis of Artifacts on Chipless RFID Backscatter Tag Signals for Real World Implementation - Grishma Khadka; Meriam Anushani Bibile; Larry M. Arjomandi; Nemai Chandra Karmakar (IEEE Access, 2019)
Chipless radio-frequency identification (RFID) has been studied as an alternative technique to conventional chipped RFID. However, chipless RFID tag backscatter signals are affected by motion and especially when they are attached to different objects. In this paper, we performed a comprehensive analysis of the backscattered chipless tag signal in two different stages. At the first stage, we performed an analysis of the backscattered signal in the nonanechoic environment when the frequency-coded tags were moving at different stepped positions. Then we continued to identify the response of signal where the chipless tag was attached to highly scattering objects. The results showed the variation in amplitude and shifting in the frequency of tag resonant when the tag was moving at different stepped positions. The variation was more prominent when the tag was attached to random objects. In order to address the issue, we conducted an experiment on orientation insensitive ground plane tag to solve the frequency shifting problem and proposed a robust detection method based on mother wavelet for the detection of tag IDs. The overall results show that the proposed technique reduces uncertainty in frequency-based chipless RFID tag signal response due to the variation in amplitude. The technique also helps in detecting the tag data bits with better resolution and has a good arrangement between time and frequency resolution for high-frequency signal components. The throughput of 90% is obtained even when the tag is attached to highly scattering objects. Finally, to validate the performance, a ground plane tag is implemented and the proposed algorithm is experimentally demonstrated.